Jejunal gastrointestinal stromal tumors masquerading as an appendicular mass: an unusual presentation - Choudhari, Rajat R.; Raghavendra, Annagiri; Kalbavi, Harish Rao (International Surgery Journal, 2020)
Gastrointestinal stromal tumors (GISTs) are a rare variety of tumors of mesenchymal origin found in the gastrointestinal (GI) tract forming about 1% of all GI tumors. These originate from the interstitial cells of Cajal. Small bowel GISTs have been shown to present as obscure GI bleeding, obstruction and perforation in literature. We report a 57 years old female patient presenting with pain abdomen, fever and vomiting and palpable right iliac fossa (RIF) mass diagnosed as an appendicular mass and managed conservatively. She was planned interval appendicectomy and was discovered to have a jejunal GIST at laparotomy treated with resection and anastomosis. There are case reports of small bowel GISTs presenting as sources of obscure or overt GI bleeding and luminal or extra luminal mass causing small bowel obstruction. Surgery is mainstay of treatment with imatinib for adjuvant or neoadjuvant therapy. This case highlights an unusual presentation of a jejunal GIST with a sealed off perforation mimicking an appendicular mass in the RIF treated by surgical resection followed by adjuvant Imatinib therapy. GIST being an uncommon tumor with varied presentations can lead to misdiagnosis and delays in treatment. This differential should be kept in mind while evaluating small bowel pathologies to aid a timely diagnosis.